2017
DOI: 10.1088/1748-9326/aa8a32
|View full text |Cite
|
Sign up to set email alerts
|

Air quality improvements and health benefits from China’s clean air action since 2013

Abstract: Aggressive emission control measures were taken by the Chinese government after the promulgation of the 'Air Pollution Prevention and Control Action Plan' in 2013. Here we evaluated the air quality and health benefits associated with this stringent policy during 2013-2015 by using surface PM 2.5 concentrations estimated from a three-stage data fusion model and cause-specific integrated exposure-response functions. The population-weighted annual mean PM 2.5 concentrations decreased by 21.5% over China during 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
119
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(127 citation statements)
references
References 33 publications
8
119
0
Order By: Relevance
“…year −1 or −7.2% year −1 . This is comparable to Zheng et al (2017), who find that the annual mean PM 2.5 across 74 Chinese cities decreased by 23.6% between 2013-2015 (−7.9% year −1 ). Lin et al (2018) used satellite data to suggest the Chinese PM 2.5 trend steepened from −0.65 μg m −3 year −1 between 2006-2010 to −2.3 μg m −3 year −1 between 2011-2015.…”
Section: Methodssupporting
confidence: 81%
“…year −1 or −7.2% year −1 . This is comparable to Zheng et al (2017), who find that the annual mean PM 2.5 across 74 Chinese cities decreased by 23.6% between 2013-2015 (−7.9% year −1 ). Lin et al (2018) used satellite data to suggest the Chinese PM 2.5 trend steepened from −0.65 μg m −3 year −1 between 2006-2010 to −2.3 μg m −3 year −1 between 2011-2015.…”
Section: Methodssupporting
confidence: 81%
“…Compared to these temporary plans, the Action Plan is China's longest-term, largest-scale, and toughest clean air policy to date. The implementation of the Action Plan has made significant achievements in both air quality improvement and public health protection, which can be evidenced from the results of our study and several other studies [18,19,39,40].…”
Section: Discussionsupporting
confidence: 69%
“…To date, several studies have been conducted at regional and national levels to evaluate the effectiveness of the Action Plan. These studies have consistently indicated the health benefits of the improved air quality following the implementation of the Action Plan [12][13][14][15][16][17][18][19]. However, such studies had limitations, as follows.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yang et al (2016) to the increasing trend of wintertime PM 2.5 concentrations averaged over eastern China from 1985China from to 2005 To improve air quality, "Air Pollution Prevention and Control Action Plan" was promulgated by Chinese government in 2013. As a consequence, observed annual mean PM 2.5 concentrations decreased by about 20% over China during (Zheng et al, 2017 due to effective reductions in major air pollutants (e.g., SO 2 and NO 2 ), for example, about 50% reduction of SO 2 over North China Plain during 2012-2015 as seen by satellite retrievals (Krotkov et al, 2016). However, observed winter severe haze events did not show reductions in recent years (Figure 1a), highlighting potential importance of atmospheric conditions in influencing the occurrence of severe haze events in winter (Cai et al, 2017).…”
Section: Introductionmentioning
confidence: 97%